Relationship between childhood traumas, cognitive distortions and aggression in forensic psychiatry patients aggression in forensic psychiatry patients - Atay, Eda; Dogan, Ufuk; Isil, Ozlem; Hekim, Buke; Kilic, Nilufer (Routledge Journals, Taylor & Francis Ltd, 2026)
Aggression is a common problem in forensic psychiatric patients and an important problem for psychiatric nurses during the treatment, care and rehabilitation of patients. The aim of this study is to determine the relationship between childhood traumas, cognitive distortions and aggression in forensic psychiatry patients. This descriptive study was conducted with 103 forensic psychiatry patients treated in a high security forensic psychiatry hospital. The data of study were collected Introductory Information Form, Childhood Psychological Traumas Scale (CTQ), Cognitive Distortions Scale (CDS) and Buss-Perry Aggression Scale (BAQ). The data of the study were collected using the Introductory Information Form, the Childhood Trauma Questionnaire (CTQ), which assesses traumatic experiences in childhood; the Cognitive Distortions Scale (CDS), which measures dysfunctional thought patterns; and the Buss-Perry Aggression Questionnaire (BAQ), which evaluates levels of aggression. The study found a significant positive correlation among childhood traumas, cognitive distortions, and aggression, indicating that higher levels of childhood trauma and cognitive distortions are associated with increased aggression. This study highlights the importance of considering both early traumatic experiences and cognitive processes together in the management and prevention of aggression among forensic psychiatric patients. The findings emphasize the necessity of taking these factors into account for risk assessment and effective treatment planning.
Keywords: Childhood traumas; cognitive distortions; aggression; forensic psychiatry; nursing